Relic of a Bygone Era? A Comparative Review of the Defence of “Reasonable Correction” in Canadian and Israeli Criminal Law - Aiyer, Rick (Revue générale de droit, 2024)
On January 25, 2000, the Supreme Court of Israel delivered its celebrated decision in Plonit. In a landmark ruling, the country’s highest court abolished the criminal law defence of “reasonable correction,” thus making Israel the first common law jurisdiction to recognize children’s right to equal protection from assault. Contrarily, in the Charter case of Canadian Foundation four years later, a majority of the Supreme Court of Canada elected to uphold a similar defence of reasonable correction in section 43 of the Criminal Code. This article therefore takes a fresh look at Canadian Foundation through the instructive lens of Plonit. It seeks, firstly, to supply an abolitionist frame of reference within which Canadian Foundation may be critically assessed. It endeavours, moreover, to buttress four minority positions expressed in Canadian Foundation: (a) section 43 offends Canada’s international commitments, (b) section 43 constitutes an unworkable criminal law standard, (c) section 43 is incongruous with a child’s right to dignity, and (d) striking down section 43 will not open the floodgates to criminal sanction for every trivial or necessary application of force. In doing so, this article concludes that section 43 of the Criminal Code has outlived not only its legal defensibility, but also its social acceptability.